Can bark stripping cause red heartwood formation in beech stems? - Račko V; Mišíková O; Hlaváč P; Deáková V (iForest - Biogeosciences and Forestry, 2018)
Injuries to standing trees caused by logging and the subsequent changes in biochemical composition and anatomy of affected tissues lead to wood quality loss, thus lowering the commercial value of roundwood. In this study, we investigated the influence of various factors that could help mitigate or prevent the spread of infections in the stem caused by injuries. A total of 112 beech logs (tree age: 42-143 years) from ten forest stands at three different sites in central Slovakia were examined, and the extent of discolouration and decay zones in each stem was measured, along with cambial age, stem diameter, injury width, and injury closure period. The results showed that the width of physiologically active wet sapwood and the width of the inactive dehydrated zone in the stem are important factors influencing red heartwood formation. We found no significant differences in the extent of discolouration and decay among different stands and sites. Stem diameter and injury width did significantly affect the penetration of infection through sapwood, and red heartwood formation was significantly affected by cambial age and injury width, while stand age, site slope, beech proportion in the stand and injury closure did not show any significant effect. Binary logistic models were applied to assess the probability of pathogen penetration through sapwood into the stem dehydrated zone as a function of injury width and stem diameter, as well as the probability that this could lead to red heartwood formation based on injury width and cambial age of beech stems.